Investing the textual approach in the learner’s psyche in light of the competency approach. - HERIZI , LAKHDAR (Journal of Social Sciences and Humanities, 2021)
This study addressed the topic of the necessity of investing the technique of textual approach and its relationship to the learner's psyche in light of the pedagogy of the approach with competencies, which the Algerian educational system adopted after the reform process in the academic year 2003/2004. Where the researcher focused on defining a set of educational terms and approaches, such as the concept of the term language approach and terminology, and the definition of the word competence in linguistic and idiomatic terms, and the concept of pedagogy of the approach with competencies in all fields in general, and in the field of education in particular, and the reasons for its selection in addition to the definition of the textual approach technique, Resorting to it, such as choosing a pedagogy in teaching languages in general, and in teaching Arabic in particular. After that, the study touched on the concept of admissibility criterion related to the learner’s psyche, and the extent of his acceptance of scientific knowledge, if it fits with his ideas and inclinations and Its stances, social and cultural environment, and intent criterion that relates to the teacher (writer) or owner of the text, as it relates to the goals that the text writer wants through his text, with an indication of the outcome of these two criteria on the success of the educational / learning process. Then the researcher moved to give the relationship between the textual approach to the student's psyche, and then the relationship between the textual approach and the approach with competencies. As it was concluded the great relationship between these pedagogical approaches with the educational text that is adopted in the textbooks addressed to pupils at all levels of education. This text must be subject to a set of pedagogical, psychological and social conditions and standards, which are related to the group of learners at each stage, and the social and cultural milieu that It contains the learner, the linguistic and cognitive content contained in the text, and the length of time the teaching process takes. Finally, the study ended with an important recommendation, which is the necessity of respecting a set of conditions and criteria that must be met in choosing the educational text directed to pupils in textbooks at a certain educational stage, as a result of the impressive results that theoretical and applied studies have proven, and which emphasized the great benefit that The learner will benefit from it in the field of teaching the language using the textual approach method, provided that this is related to the student's desires, aspirations and needs